LITERASI DIGITAL INDONESIA SEBAGAI TANTANGAN DEMOKRASI DI ERA DIGITAL - Bulya, Bulya; Izzati, Suci (The Journal of Society and Media, 2024)
In the era of digitalization, digital literacy plays a vital role in shaping active participation and the quality of democracy. There are still challenges in the level of digital literacy in Indonesia, which impacts blind trust in emerging issues. As a result, people are vulnerable to the spread of fake news, online fraud, harmful content, and privacy violations. This research uses a desk research method with a qualitative approach, collecting secondary data from journal articles, books, and related reports. Analyses were conducted using content analysis techniques to identify patterns and relationships between digital literacy and democracy. The results show that although Indonesia's digital literacy index has improved, digital crime and hoaxes are rising, indicating a gap between technological skills and digital ethics. The findings emphasize the need for a more comprehensive approach to digital literacy programs, including integrating digital literacy education into the formal curriculum and improved technological infrastructure, particularly in underdeveloped areas. The implications of this study suggest that improving digital literacy is essential for safe access to information and an important step toward strengthening more critical and responsible democratic participation in Indonesia.